A molecular atlas reveals the tri-sectional spinning mechanism of spider dragline silk - Wenbo Hu; Anqiang Jia; Sanyuan Ma; Guoqing Zhang; Zhaoyuan Wei; Fang Lu; Yongjiang Luo; Zhisheng Zhang; Jiahe Sun; Tianfang Yang; TingTing Xia; Qinhui Li; et al. (Nature Communications, 2023)
The genetic basis of spider major ampullate (Ma) gland silk production remains unknown. Hu et al. unveil a molecular atlas of this gland for the golden orb-weaving spider combining genome assembly and multiomics, revealing the single-cell spatial architecture of silk production in the Ma gland.